DIC SYNDROM and THROMBOTIC PATHOLOGIES DURING PREGNANCY AND THEIR HEMORRHAGIC INDICATIONS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
One of the most actual medical problems is the health of reproductive women and newborns. This issue is important not only in Uzbekistan, but on a global scale, and causes the increase in the death of mothers and children, disability.